ARTIFICIAL INTELLIGENCE AS A CO-LEGISLATOR: THE IDEA OF HARMONIZING LAWS AND REGULATIONS TOWARDS SMART LAWMAKING - Adhe Ismail Ananda (Domus Legalis Cogitatio, 2026)
The rapid advancement of Artificial Intelligence (AI) presents new opportunities within legal systems, particularly in the harmonization of laws and regulations, which has long been challenged by complexity, regulatory overlaps, and normative disharmony. This article introduces the concept of AI as Co-Legislator, positioning AI not merely as a technical instrument but as a strategic partner in the process of lawmaking and regulatory harmonization. Through the capabilities of machine learning and natural language processing, AI can analyze thousands of regulations, detect potential normative conflicts, and provide data-driven recommendations to accelerate the creation of effective, efficient, and coherent legal frameworks. This idea aligns with the paradigm of smart lawmaking, which envisions adaptive, responsive, and technology-based legislation that upholds the principles of legal certainty, justice, and utility. The research employs a normative-juridical method with a conceptual approach, combining legal analysis with technological innovation perspectives. The findings suggest that while employing AI as a co-legislator has significant potential to enhance the quality of legal harmonization, ethical, juridical, and institutional challenges must be addressed, including issues of legitimacy, accountability, and data protection. Therefore, integrating AI into the harmonization of laws should be positioned as an innovative step toward building a smart legal system without diminishing the sovereignty of human legislators.